KESALAHAN BENTUKAN KATA BERAFIKS DALAM KARANGAN MAHASISWA THAILAND YANG BERBAHASA IBU BAHASA MELAYU - Robeeyah Bueraheng; Imam Suyitno; Gatut Susanto (Graduate School of Universitas Negeri Malang, 2017)
The aim of this study is to describe the error of affixed word formation by Thai students who speak Malay as their mother tongue that covers (1) the error of affixed word formation as viewed from context sentence, (2) the error of affixed word formation as viewed from the natural use of words. This research design being use in this study is qualitative research design and the researcher employs essay writing technique as the main data collection. The findings indicate that the Thai students who speak Malay as their mother tongue performed the error of affixed word formation as viewed from context sentence. The findings pointed out some errors that covered (1) affixes omission (prefixes, suffixes and circumfix), (2) affixes addition (prefixes and suffixes), and (3) affixes ambiguity usage (prefixes and circumfix). Furthermore, based on the context sentence, the researcher found that there were errors of affixed word formation as viewed from the natural use of words. These issues caused by the use of unnatural words, such as permula kali, bergaulan, mengirimkan, berhormat, berziarah, berbual, kedudukan, berhubungan siraturrahmi, tersoho, bercakap.Penelitian ini bertujuan untuk mendeskripsikan kesalahan bentukan kata berafiks dalam karangan mahasiswa Thailand yang berbahasa ibu bahasa Melayu, meliputi (1) kesalahan bentukan kata berafiks ditinjau dari konteks kalimat dan (2) kesalahan bentukan kata berafiks ditinjau dari kelaziman penggunaan kata. Metode yang digunakan adalah kualitatif dengan teknik penugasan menulis karangan. Hasil temuan penelitian ini menunjukkan bahwa mahasiswa Thailand yang berbahasa Ibu bahasa Melayu banyak melakukan kesalahan bentukan kata berafiks ditinjau dari konteks, meliputi (1) penghilangan afiks (prefiks, sufiks, dan konfiks), (2) penambahan afiks (prefiks dan sufiks), dan (3) kerancuan penggunaan afiks (prefiks dan konfiks). Selanjutnya, kesalahan bentukan kata berafiks ditinjau dari kelaziman penggunaan kata. Hal ini terjadi karena penggunaan kata-kata yang tidak lazim, seperti permula kali, bergaulan, mengirimkan, berhormat, berziarah, berbual, kedudukan, berhubungan siraturrahmi, tersoho, bercakap.